2019
DOI: 10.1093/hmg/ddz102
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific abnormalities in the visual system of a mouse model of CDKL5 deficiency disorder

Abstract: CDKL5 deficiency disorder (CDD) is a neurodevelopmental disorder characterized by a severe global developmental delay and early-onset seizures. Notably, patients show distinctive visual abnormalities often clinically diagnosed as cortical visual impairment. However, the involvement of cerebral cortical dysfunctions in the origin of the symptoms is poorly understood. CDD mouse models also display visual deficits, and cortical visual responses can be used as a robust biomarker in CDKL5 mutant mice. A deeper unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 41 publications
(60 reference statements)
6
34
0
Order By: Relevance
“…However, the protein level of PSD-95, a CDKL5-interacting protein in the postsynaptic density, appeared to be reduced in pups lacking CDKL5 (0.812 ± 0.049 of WT, p < 0.01; Fig. 7A, D), consistent with previous studies in mutant mice and in cultured neurons (Ricciardi et al, 2012;Zhu et al, 2013;Della Sala et al, 2016;Pizzo et al, 2016;Lupori et al, 2019). Thus, KCC2 phosphorylation at S940 appears to be selectively down-regulated in Cdkl5 null pups, especially at the age when they are suffering from spontaneous seizures.…”
Section: Reduced Functional Kcc2 In Cdkl5 -/Y Cortex At P12supporting
confidence: 90%
“…However, the protein level of PSD-95, a CDKL5-interacting protein in the postsynaptic density, appeared to be reduced in pups lacking CDKL5 (0.812 ± 0.049 of WT, p < 0.01; Fig. 7A, D), consistent with previous studies in mutant mice and in cultured neurons (Ricciardi et al, 2012;Zhu et al, 2013;Della Sala et al, 2016;Pizzo et al, 2016;Lupori et al, 2019). Thus, KCC2 phosphorylation at S940 appears to be selectively down-regulated in Cdkl5 null pups, especially at the age when they are suffering from spontaneous seizures.…”
Section: Reduced Functional Kcc2 In Cdkl5 -/Y Cortex At P12supporting
confidence: 90%
“…Animals were fixed under the objective using a magnet mounted on an arduino-based imaging chamber. Red light illumination (630 nm) was obtained with 8 individually addressable LEDs (WS2812) secured to the objective (Leica PanApo 2.0X 10447170) by a custom 3D printed holder 41 . Visual stimuli were generated using Matlab Psychtoolbox and displayed on a screen placed 13 cm away from the eyes of the animals.…”
Section: Methodsmentioning
confidence: 99%
“…EEG and sensory-evoked responses are readily applicable to humans and widely used for non-invasive assessment of cortical function, making electrophysiological measurements or functional imaging ecologically ideal translational tools for functional analyses in children with neurodevelopmental disorders ( Nelson and McCleery, 2008 ; Lloyd-Fox et al , 2010 ; Vanderwert and Nelson, 2014 ). Accordingly, previous studies reported that a standardized inspection of EEG and cortical responses to sensory stimuli is suitable to reveal, in both animal models and patients, stage-specific alterations in other disorders affecting neurodevelopment ( Bosl et al , 2011 ; Durand et al , 2012 ; LeBlanc et al , 2015 ; Boggio et al , 2016 ; Mazziotti et al , 2017 ; Bowman and Varcin, 2018 ; Lupori et al , 2019 ). Abnormal EEG waveforms have been previously documented in creatine transporter deficiency patients, indicating diffuse slowing, interictal theta activity, specific sharp abnormalities and focal/generalized paroxysmal or slow abnormalities ( Schiaffino et al , 2005 ; Póo-Argüelles et al , 2006 ; Mancardi et al , 2007 ; Fons et al , 2009 ; Leuzzi et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%